Awareness of ovarian cancer symptoms and risk factors in a young ethnically diverse British population - Cristina‐Alexandra Radu; Nadia Matos de Melo Fernandes; Sumaira Khalfe; Britta Stordal (Cancer Medicine, 2023)
Abstract Background Ovarian cancer does not cause many symptoms in the early stages, which is why the majority of cases are of advanced disease. Increasing awareness of ovarian cancer symptoms may lead to earlier diagnosis and improved outcomes. Methods Participants in Britain completed the Ovarian Cancer Awareness Measure by online survey (n = 459). Results Our participants were 75% female, 25% male and a young (27.89 ± 11.44 years) ethnically diverse population (40.3% White, 29.3% Asian and 18.0% Black). Individuals recalled 1.24 ± 1.30 symptoms, and recognised 5.96 ± 2.4 symptoms. We found higher levels of recall and recognition compared to previous research possibly due to using an online survey. Recognition was lowest for difficulty eating (39.4%) and persistently feeling full (38.7%). Males had slightly lower symptom recall and recognition than females. Participants incorrectly recalled an irregular menstrual cycle (22.4%) as an ovarian cancer symptom and 67% answered the age of incidence question incorrectly. Suggesting that participants incorrectly associate ovarian cancer as a disease of pre‐menopausal women. Individuals recalled 1.47 ± 1.20 risk factors, and recognised 6.1 ± 2.4 risk factors. Family history of ovarian cancer was recalled by 59% of participants. Recognition was lowest for in vitro fertilisation treatment (23.0%) and talcum powder in the genital area (23.0%). The generic cancer risk factors of alcohol (9.3%) and poor diet (8.8%) were recalled as specific ovarian cancer risk factors. 57.9% of participants incorrectly answered that there is an ovarian cancer screening programme. Suggesting confusion between ovarian and cervical cancer as participants also recalled cervical cancer risk factors of sexually transmitted diseases (6.3%) and human papillomavirus (1.5%). 29.7% of female participants would seek help for an ovarian cancer symptom within 1–2 days. Help seeking was higher in the Black and Asian ethnicities (44.4% and 45.0%; p = 0.018). Conclusion Awareness of ovarian cancer symptoms is low. Ovarian cancer awareness campaigns should include common misconceptions identified in this research.